Kinerja Stabilisasi Campuran Aspal Panas AC-WC Menggunakan Aspal Modifikasi (Elastomer) dengan Penambahan Lateks - Haikal Fikri Da'fa Nurcahyo; Sartika Nisumanti; Khodijah Al Qubro (Jurnal Talenta Sipil, 2026)
Pavements in Indonesia often experience damage before the planned service life is reached, one of which is caused by permanent deformation due to excessive load pressure, such as that produced by heavy vehicles. This study aims to analyze the effect of latex addition on the characteristics of AC-WC pavement type asphalt mixtures using elastomer modified asphalt. The use of asphalt is varied in five levels, namely 4%, 4.5%, 5%, 5.5%, and 6% of the total aggregate weight. The AC-WC mixture manufacturing process refers to the 2018 Bina Marga specifications (Revision 2). The results showed that the addition of latex affected the characteristics of the Marshall value in the asphalt mixture compared to conventional asphalt, where the VMA value with latex additives decreased by 1% at a latex content of 5% with a value of 18.029. The VFA value decreased by 1% at a latex content of 5% with a value of 73.805. The VIM value in this mixture is still within the required specifications, which is between 3% and 5%. The stability value increased significantly at 7% latex content with a value of 3249.7, while the MQ value increased significantly at 7% latex content with a value of 2214.137. From the results of the study, it can be concluded that asphalt containing latex has better durability compared to conventional asphalt, so it can be used as an alternative to improve the quality of road pavement in Indonesia.